Design and Analysis of a Graded-Index Strained Si $_{1-x}$ Ge $_x$ Optical PN Phase Shifter - Darpan Mishra; Ramesh Kumar Sonkar (IEEE Photonics Journal, 2018)
In this paper, a graded-index strained Si1-xGex optical PN phase shifter with multiple strained layers has been proposed for high speed data modulation at 1550 nm with low device footprint. The quasi-vectorial finite difference method, non-local empirical pseudopotential method and the Payne-Lacey model has been used to analyze the proposed device. A phase shift of 122°/mm, VπLπ of 0.74 V.cm, and insertion loss of 4 dB at 5 V reverse bias with a 3-dB modulation bandwidth of 27.5 GHz has been obtained for a 500 nm x 250 nm cross-section rib waveguide with 50 nm slab. A 15°/mm increase in phase shift and 0.08 V.cm decrease in VπLπ has been observed when the junction is shifted by 60 nm towards the N side.